Injuries of the trachea and bronchi - Bertelsen, S. (1972)
Traumatic rupture of the trachea or the bronchi is reported with increasing frequency. Such rupture may follow penetrating wounds, but the common cause is blunt trauma of the throat or thorax. When the proximal trachea is damaged other cervical structures are usually involved. By contrast the distal trachea or bronchi are not infrequently the only thoracic structures damaged. In particular there may be no rib fractures, or obvious fractures may be uncomplicated and insignificant. Thoracic rupture usually occurs in the vicinity of the carina. Central rupture generally presents with emphysema of the mediastinum and neck. Diagnosis can usually be confirmed by tracheobronchoscopy. Rupture of the peripheral bronchi generally presents with pneumothorax and atelectasis. Central rupture should be treated by primary suture. Lobectomy is often necessary when small bronchi are ruptured.